Fish Slaughter, Killing, and Euthanasia: A Review of Major Published U.S. Guidance Documents and General Considerations of Methods - Roy P. Yanong; Kathleen H. Hartman; Craig A. Watson; Jeffrey E. Hill; B. Denise Petty; Ruth Francis-Floyd (EDIS)
Circular 1525, a 6-page fact sheet by Roy P.E. Yanong, Kathleen H. Hartman, Craig A. Watson, Jeffrey E. Hill, B. Denise Petty, and Ruth Francis-Floyd, provides a discussion of terminology used to describe the deliberate ending of life of a fish, reviews of four major guidance documents with the limitations of each, and a discussion of general considerations. Includes references. Published by the UF Department of Fisheries and Aquatic Sciences, June 2007.